2005
DOI: 10.1097/01.fpc.0000174789.77614.68
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin K epoxide reductase complex 1 (VKORC1) variants with warfarin dose in a Hong Kong Chinese patient population

Abstract: VKORC1 genotype is the dominant genetic influence on inter-individual variability in warfarin dose in Hong Kong Chinese. The lower mean dose of warfarin in Chinese, relative to Europeans, appears to be a reflection of their preponderance of the 'low-dose' VKORC1 H1/H1 (homozygous group A) genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
107
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(120 citation statements)
references
References 17 publications
10
107
0
3
Order By: Relevance
“…Most studies focused on FGB polymorphisms. However, results are not consistent and none of these polymorphisms has been found to be associated with an increased risk of venous [6,7] or arterial thrombosis [7]. Recently, we reported that a specific haplotype (H2) of the fibrinogen gamma gene (FGG) was associated with a 2.4-fold increased risk of deep venous thrombosis [95% confidence intervals (CI): 1.5-3.9] [6].…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Most studies focused on FGB polymorphisms. However, results are not consistent and none of these polymorphisms has been found to be associated with an increased risk of venous [6,7] or arterial thrombosis [7]. Recently, we reported that a specific haplotype (H2) of the fibrinogen gamma gene (FGG) was associated with a 2.4-fold increased risk of deep venous thrombosis [95% confidence intervals (CI): 1.5-3.9] [6].…”
mentioning
confidence: 83%
“…Population differences of VKORC1 haplotype and CYP2C9 genotype frequencies have also been suggested from initial studies [1,4,6]. We identified the frequency of genotype combinations across world populations of the four haplotype tag SNPs for VKORC1 described by Reider et al [1] (861, 5808, 6853, and 9041) and CYP2C9 (*2 and *3) using Pyrosequencing [1,4] in 556 unrelated healthy individuals from the following populations: European-American, African, African-American, Hispanic (Mexican and Peruvian) and Asian (Table 1).…”
mentioning
confidence: 99%
“…Luego se detectaron el polimorfismo -1639G>A en el gen VKORC1 y los polimorfismos 430C>T (*2) y 1075A>C (*3) en el gen CYP2C9 mediante PCR en tiempo real, utilizando el sistema fluorescente LightMix 庐 de Roche, como se ha descrito previamente (23,24). En resumen, durante la amplificaci贸n de fragmentos espec铆ficos de 289 pares de bases para el VKORC1 y de 374 y 180 pares de bases para el CYP2C9, se logr贸 la hibridaci贸n de las sondas fluorog茅nicas.…”
Section: Genotipificaci贸nunclassified
“…Veenstra et al 60 reported on the combined effect of CYP2C9 and VKORC1 allelic variants. Among patients with the VKORC1AA haplotype in a Hong Kong Chinese population, 4 (5.8%) were heterozygous for CYP2C9*3 and had a lower dose requirement (1.9 mg/d) than patients who exhibited the CYP2C9*1/*1 genotype (3.0 mg/d).…”
Section: Effect Of Allelic Variants On Warfarin Activitymentioning
confidence: 99%